Glioblastoma patients in Slovenia from 1997 to 2008 - Smrdel, Uroš (Radiology and oncology (Ljubljana), 2014)
Glioblastoma is the most common primary brain tumour. It has a poor prognosis despite some advances in treatment that have been achieved over the last ten years. In Slovenia, 50 to 60 glioblastoma patients are diagnosed each year. In order to establish whether the current treatment options have any influence on the survival of the Slovenian glioblastoma patients, their data in the period from the beginning of the year 1997 to the end of the year 2008 have been analysed. Patients and methods. All patients treated at the Institute of Oncology Ljubljana from 1997 to 2008 were included in the retrospective study. Demographics, treatment details, and survival time after the diagnosis were collected and statistically analysed for the group as a whole and for subgroups. Results. From 1997 to 2008, 527 adult patients were diagnosed with glioblastoma and referred to the Institute of Oncology for further treatment. Their median age was 59 years (from 20 to 85) and all but one had the diagnosis confirmed by a pathologist. Gross total resection was reported by surgeons in 261 (49.5%) patients; good functional status (WHO 0 or 1) after surgery was observed in 336 (63.7%) patients, radiotherapy was performed in 422 (80.1%) patients, in 317 (75.1%) of them with radical intent, and 198 (62.5 %) of those received some form of systemic treatment (usually temozolomide). The median survival of all patients amounted to 9.7 months. There was no difference in median survival of all patients or of all treated patients before or after the chemo-radiotherapy era. However, the overall survival of patients treated with radical intent was significantly better (11.4 months; p < 0.05). A better survival was also noticed in radically treated patients who received additional temozolomide therapy (11.4 vs. 13.1 months; p = 0.014). The longer survival was associated with a younger age and a good performance status as well as with a more extensive tumour resection. In patients treated with radical intent, having a good performance status, and receiving radiotherapy and additional temozolomide therapy, the survival was significantly longer, based on multivariate analysis.
Keywords: glioblastom; glioblastoma; kirurgija; preživetje; radioterapija; radiotherapy; surgery; survival; termozolomid; termozolomide; therapy; treatment; zdravljenje